2017
DOI: 10.1021/acs.jpclett.7b01367
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nonhydrostatic Stress on Structural and Optoelectronic Properties of Methylammonium Lead Bromide Perovskite

Abstract: We report synchrotron X-ray diffraction, photoconductivity, and photoluminescence investigations of methylammonium-lead-bromide (MAPbBr) under various stress conditions, supported by density-functional-theory (DFT) calculations. The properties of MAPbBr show substantial dependence on the hydrostatic conditions. While nonhydrostatic compression of MAPbBr leads to amorphization above 2.4 GPa, under quasi-hydrostatic (Ar) and hydrostatic (He) pressure, the sample remains in crystalline phases. A sequence of phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
70
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 55 publications
8
70
0
Order By: Relevance
“…It is worth noting that the generation of residual stress during the fabrication process is induced by lattice mismatch, which also influences electronic characters and stability of the device . In the initial spin coating process, the interaction between the crystal nuclei in the precursor solution is so weak that the viscosity is not high enough to sustain the stress and the crystal nuclei in the precursor solution can move freely, as shown in Figure S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the generation of residual stress during the fabrication process is induced by lattice mismatch, which also influences electronic characters and stability of the device . In the initial spin coating process, the interaction between the crystal nuclei in the precursor solution is so weak that the viscosity is not high enough to sustain the stress and the crystal nuclei in the precursor solution can move freely, as shown in Figure S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…However, at lower laser scanning speed, the movement of cations in the perovskite crystal is promoted and concentrated at the defects and grain boundaries, leading to an uneven distribution of the potential field in the MAPbI 3 film and forming a large number of positive and negative electric centers in the film. At the same time, MAPbI 3 perovskite films will decompose to PbI 2 crystals, while MAI will decompose into CH 3 NH 2 and HI (Figure S1a, Supporting Information) . Here we focus on the (110) crystallization peak of the XRD pattern to demonstrate crystal structure changes in the MAPbI 3 perovskite film (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, a number of studies have studied the physical behavior of 3D hybrid halide perovskites under extreme hydrostatic pressures using diamond anvil cell (DAC) chamber design . These pressure studies provide a powerful tool for changing interatomic distances and bond lengths on demand, and monitor structural, physical, or chemical properties and functionalities at finite pressures.…”
Section: Summary Of Experimental and Theoretical Bandgap Values For 2mentioning
confidence: 99%
“…Previous studies [26][27][28] revealed that pure ILs have an anisotropic cluster structure, and the hydrogen-bonding network can be easily disturbed by adding various materials under high-pressure conditions. Deemyad et al [29][30][31] concluded that pressure can induce superconductivity and electronic properties modification of Cu 2 I 2 Se 6 by a structural change. The electronic responses, optoelectronic properties, energy band gaps, and crystal structures of different materials, such as semiconductors [29], perovskites [30], and piezochromic materials [31], can be varied by compression.…”
mentioning
confidence: 99%
“…Deemyad et al [29][30][31] concluded that pressure can induce superconductivity and electronic properties modification of Cu 2 I 2 Se 6 by a structural change. The electronic responses, optoelectronic properties, energy band gaps, and crystal structures of different materials, such as semiconductors [29], perovskites [30], and piezochromic materials [31], can be varied by compression. For example, IL-β-cyclodextrin (IL-β-CD) associated forms under low pressures can be turned to dissociated structures with the pressure increase [26].…”
mentioning
confidence: 99%